Research and development of the suction component for gripping various surfaces - Kazushi SHIBATA; Yuto SAWADA; Satoshi ASHIZAWA; Kenichi OOHARA; Toshio FUKUDA; Takeo OOMICHI (Nihon Kikai Gakkai ronbunshu, 2020)
In recent years, robots are increasingly used for rescue activities and inspections at disaster sites. However, many robots have limited adaptive environment, and there are still problems in actual use. We are studying vacuum suction, which is considered to be able to adsorb to various objects among suction components. There were many problems with conventional suction component. For example, suction part using a flexible material is weak to the load from the shear direction of the suction surface. In this paper, the suction force generated from the suction surface is divided into the suction force and the retention force by the suction area. By separating the suction force and the retention force, the retention force almost holds the suction surface, but the suction force holds a part of it. As a result, a large load can be held in the rigid part, and the durability is improved. By separating the suction mechanism and the retention mechanism with bellows, it is possible to correct the difference between the coordinates of the suction pad and the coordinates of the hand of the robot, and there is also an advantage when mounting the suction component on the robot. When the impact load falls on the robot, the bellows can recover the suction state in the time it takes to extend due to the bellows. Also, conventional suction components were limited of suction surface. Therefore, we develop composite sealing material to adsorb more variable surface. We show the improvement of adaptability to granite, concrete blocks, tile with grooves, and so on by applying this material. We report on useful findings from the results and discussion.